2019
DOI: 10.1364/ol.44.001730
|View full text |Cite
|
Sign up to set email alerts
|

Watt-scale 50-MHz source of single-cycle waveform-stable pulses in the molecular fingerprint region

Abstract: We report a coherent mid-infrared (MIR) source with a combination of broad spectral coverage (6-18 μm), high repetition rate (50 MHz), and high average power (0.5 W). The waveform-stable pulses emerge via intrapulse differencefrequency generation (IPDFG) in a GaSe crystal, driven by a 30-W-average-power train of 32-fs pulses spectrally centered at 2 μm, delivered by a fiber-laser system. Electro-optic sampling (EOS) of the waveform-stable MIR waveforms reveals their single-cycle nature, confirming the excellen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 26 publications
0
48
0
Order By: Relevance
“…By phase matching in a suitable nonlinear medium, opposite wings of the broad input spectrum can mix and generate photons in the MIR. Recently IDFG has been shown to afford conversion efficiencies greater than 1% while maintaining more than one octave of bandwidth [41,42]. In particular, by driving with a central wavelength of 2 μm it is possible to take advantage of the higher damage threshold and broader phase matching bandwidth provided by crystals such as gallium selenide (GaSe), while exploiting a lower quantum defect [56].…”
Section: Intra-pulse Dfg In Gasementioning
confidence: 99%
See 3 more Smart Citations
“…By phase matching in a suitable nonlinear medium, opposite wings of the broad input spectrum can mix and generate photons in the MIR. Recently IDFG has been shown to afford conversion efficiencies greater than 1% while maintaining more than one octave of bandwidth [41,42]. In particular, by driving with a central wavelength of 2 μm it is possible to take advantage of the higher damage threshold and broader phase matching bandwidth provided by crystals such as gallium selenide (GaSe), while exploiting a lower quantum defect [56].…”
Section: Intra-pulse Dfg In Gasementioning
confidence: 99%
“…EOS works through the combination of heterodyne detection and a sum-frequency generation of the MIR beam with the time delayed probe pulse, providing a direct time-domain measurement of the idler electric field [58]. Our previous work has shown that the generated MIR pulse train is waveform-stable, with a sub-100 fs duration compressible to a single cycle [42]. Through the Fourier transform of the field, the full spectrum of the MIR pulse can be measured, spanning from approximately 5 to 18 μm (see figure 7).…”
Section: Intra-pulse Dfg In Gasementioning
confidence: 99%
See 2 more Smart Citations
“…In particular, laser systems delivering trains of pulses with durations of a few tens of femtoseconds, multi-10 MHz repetition rates, and several tens of watts of average power are available today, both at 1 [4,5] and 2 μm [6,7] central wavelengths. Via parametric frequency downconversion in suitable nonlinear crystals [8], these lasers have recently established a new class of MIR radiation sources [9][10][11][12][13][14], combining broad spectral coverage with brilliance values exceeding, even those of third-generation synchrotrons [11,14], as well as with excellent temporal coherence [15,16].…”
mentioning
confidence: 99%